A citizen's guide to terrorism and counterterrorism - Harmon, Christopher C. (New York : Routledge, 2021)
"A Citizen's Guide to Terrorism and Counterterrorism, Second Edition Christopher C. Harmon This Citizen's Guide addresses the public policy issues of terrorism and counterterrorism in the United States. Written for the thinking citizen and student alike, this succinct and up-to-date book takes a "grand strategy" approach toward terrorism and uses examples and issues drawn from present-day perpetrators and actors. Christopher Harmon, a veteran academic of military theory who has also instructed U.S. and foreign military officers, organizes his book into three sections. He first introduces the problem of America's continued vulnerability to terrorist attack. Part II examines the varied ways in which the U.S. is fighting terrorism, highlighting the labors of diverse experts, government offices, intelligence and military personnel, and foreign allies. The book outlines the various aspects of the U.S. strategy, including intelligence, diplomacy, public diplomacy, economic counterterrorism, and law and law-making. In Part III, Harmon sketches the prospects for further action, steering clear of simple partisanship and instead listing recommendations with pros and cons and also including factual stories of how individual citizens have made a difference in the national effort against terrorism. New to the Second Edition Adds coverage of the Islamic State, explained in terms of its character, rise, and relative collapse under Coalition pressures. Focuses on the growing right-wing terrorist threat, domestically as well as internationally. Covers additional schools of militancy including anarchism; variants of communism and especially Maoist insurgency; and the Iranian/Shia terrorist threat throughout the Middle East and Europe, among others. Analyzes the current published White House strategy for countering terrorism"--
Part 1. The Threat. We Americans remain vulnerable to terrorist attack -- Our enemies of today -- Part 2. The Strategy. Components of our grand strategy -- The published counterterrorism strategy -- Part 3. The Future. What needs to be done -- What citizens can do -- How past terrorist groups were defeated.
First edition published 2014.
OCLC-licensed vendor bibliographic record.
Keywords: Terrorism -- United States; Terrorism -- United States -- Prevention; Security, National -- United States; POLITICAL SCIENCE / General; POLITICAL SCIENCE / Political Freedom & Security / Terrorism